Robot-assisted reconstruction using ureteroureterostomy and Lich–Gregoir ureteral reimplantation for complicated duplex kidneys in children - Huazhang Liu; Chang Tao; Xiang Yan; Guangjie Chen; Guangping Zeng (PLoS ONE, 2026)
Objective This study aimed to evaluate the efficacy of robot-assisted reconstruction using end-to-side ureteroureterostomy (UU) and Lich‒Gregoir ureterovesical reimplantation (UR) for complicated duplex kidneys in children. Methods A retrospective study was conducted on pediatric patients who underwent combined robotic UU and Lich‒Gregoir UR between January 1, 2021, and January 1, 2024. The inclusion criterion was the presence of concurrent upper- and lower-pole ureteral pathologies. Surgical time, postoperative length of stay, pre- and postoperative anteroposterior diameter of the renal pelvis (APD), ureteral diameter (UD), renal function (RF) of the affected kidney, and complications were analyzed. Results In total, 12 patients presented with urinary tract infections (UTI, n = 9), incontinence (n = 2), and abdominal pain (n = 1). Upper-pole pathologies included ectopic ureters (10 cases) and ureteroceles (2 cases). Lower-pole pathologies comprised ureteral stricture (n = 4) and vesicoureteral reflux (VUR, n = 8). The median surgical time was 177.5 minutes (range: 140–205 minutes), and the median hospital stay was 5 days (range: 3–7 days). Postoperative complications included two cases of UTI, both managed conservatively. At a median follow-up of 19 months (range: 12–31 months), no anastomotic stricture, urinary leakage, or ureteral stump syndrome occurred. Postoperative voiding cystourethrogram (VCUG) revealed no VUR in any patient. Pre- and postoperative APD (22.92 ± 9.07 mm vs. 7.33 ± 5.03 mm, p < 0.001) and UD (11.08 ± 3.15 vs. 5.83 ± 2.41 mm, p < 0.001) differed significantly in the upper pole system, as did the lower pole APD (14.00 ± 6.25 vs. 5.25 ± 3.02 mm, p < 0.001) and UD (7.75 ± 2.26 vs. 4.75 ± 1.36 mm, p = 0.003). The RF of the affected moiety improved significantly (36.58 ± 4.66% vs. 42.75% ± 3.10%, p < 0.001). Conclusions Robot-assisted reconstruction using UU and Lich–Gregoir UR is a safe and effective approach for complex duplex kidneys requiring concurrent upper- and lower-tract reconstruction, demonstrating durable resolution of obstruction and reflux as well as functional preservation.